2016
DOI: 10.1121/1.4942404
|View full text |Cite
|
Sign up to set email alerts
|

Wind turbine sound pressure level calculations at dwellings

Abstract: This paper provides calculations of outdoor sound pressure levels (SPLs) at dwellings for 10 wind turbine models, to support Health Canada's Community Noise and Health Study. Manufacturer supplied and measured wind turbine sound power levels were used to calculate outdoor SPL at 1238 dwellings using ISO [(1996). ISO 9613-2−Acoustics] and a Swedish noise propagation method. Both methods yielded statistically equivalent results. The A- and C-weighted results were highly correlated over the 1238 dwellings (Pearso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…The results were presented in six publications, addressing effects on sleep, stress, quality of life, noise annoyance and health effects and a separate paper on the effect of shadow flicker on annoyance. Also, two papers were published describing the assessment of sound levels near wind turbines and near receivers [82,83]. The Japanese study by Kakeyama et al [66,67] pertains a field study with structured face-to-face interviews at 34 study sites and 16 control sites.…”
Section: Evidence Since 2015 Based On New Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The results were presented in six publications, addressing effects on sleep, stress, quality of life, noise annoyance and health effects and a separate paper on the effect of shadow flicker on annoyance. Also, two papers were published describing the assessment of sound levels near wind turbines and near receivers [82,83]. The Japanese study by Kakeyama et al [66,67] pertains a field study with structured face-to-face interviews at 34 study sites and 16 control sites.…”
Section: Evidence Since 2015 Based On New Studiesmentioning
confidence: 99%
“…However, studying the effects of the low frequencies separately from the higher frequencies is not easy as both frequency ranges automatically go together: wind turbines all have very much the same sound composition. In a Canadian study on wind turbines, the sound levels at the facades of dwellings were calculated as both A-and C-weighted sound levels, but this proved not to be an advantage as the two were so closely linked that there was no added value in using both [82]. A limit in Aweighted decibels (where the A-weighting mimics human hearing at moderate sound levels) thus automatically limits the low-frequency part of the sound [105].…”
Section: Audibility Of Infrasound and Low-frequency Soundmentioning
confidence: 99%
“…The calculation in the software was based on the ISO 9613 [41] sound propagation standard. The accuracy of this standard for wind turbine noise calculation has been stated in several studies, by investigating the agreement between calculated and measured sound pressure level (SPL) at distances up to 2km downwind of the turbines [42,43]. It has been found that the calculation accurately determined the noise levels at 400m source-receiver distance and underestimated the measured level by 3 dB at distances of 1-2 km [42].…”
Section: Wind Turbine Noise Simulationmentioning
confidence: 99%
“…One way of accounting for inaccuracies in propagation models currently used for wind farm noise predictions is to undertake uncertainty estimates and report these along with predicted data at sensitive receiver locations [73]. Some researchers have made estimates of uncertainty for standard propagation models (±4 dBA) [74] and turbine sound power measurements (±2 dBA) [50] but more research is needed to validate the results. There are two types of uncertainty used for propagation model predictions that are sometimes confused.…”
Section: Uncertaintymentioning
confidence: 99%